The Role of Digital Marketing, Customer Orientation, and Entrepreneurial Orientation on the Marketing Performance of Muslim Fashion SMEs in Yogyakarta. - Juliani, Juliani; Nuvriasari, Audita (Formosa Journal of Science and Technology, 2024)
This research aims to explore the impact of digital marketing, customer orientation, and entrepreneurial orientation on the marketing performance of Muslim fashion SMEs in Yogyakarta. Utilizing 40 participants as a sample and employing questionnaires as the research tool, it applies a non-probability sampling strategy. The findings of this study indicate that: First, digital marketing in the Muslim fashion sector in Yogyakarta has a positive and significant effect on marketing performance. Second, marketing performance in the Muslim fashion sector in Yogyakarta is not significantly influenced by customer orientation. Lastly, entrepreneurial orientation in the Muslim fashion sector in Yogyakarta has a positive and significant effect on marketing performance.